2022
DOI: 10.1155/2022/3773625
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Waves of COVID-19 in Critically Ill Patients: A Retrospective Observational Study

Abstract: Background. The SARS-CoV-2 virus caused the global COVID-19 pandemic, with waxing and waning course. This study was conducted to compare outcomes in the first two waves, in mechanically ventilated patients. Methods. This retrospective observational study included all mechanically ventilated COVID-19 patients above 18 years of age, between March 2020 and January 2021. Patients were grouped into first wave from March 2020 to July 2020, and second wave from August 2020 to January 2021. Outcome measures were morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Compared to others etiologies, the incidence and severity of COV-AKI appears to be higher than that reported in other settings such as community acquired pneumonia or sepsis [ 30 , 31 ], especially when considering the first wave [ 26 , 27 ]. Kolhe et al.…”
Section: Acute Kidney Damage Associated With Covid-19mentioning
confidence: 79%
See 1 more Smart Citation
“…Compared to others etiologies, the incidence and severity of COV-AKI appears to be higher than that reported in other settings such as community acquired pneumonia or sepsis [ 30 , 31 ], especially when considering the first wave [ 26 , 27 ]. Kolhe et al.…”
Section: Acute Kidney Damage Associated With Covid-19mentioning
confidence: 79%
“…The incidence and severity of AKI (AKI requiring dialysis) decreased over time and across COVID-19 waves, with the first wave being more severe [ 2 , 26 , 27 ]. These results could indicate, on the one hand, a reduction in the virulence of SARS-CoV-2 due to multiple mutations and, on the other hand, the impact of vaccination in creating collective immunity beyond natural infection and the improvement in the management of COVID-19 with the introduction of corticosteroids in the treatment of severe cases of COVID-19 [ 28 , 29 ].…”
Section: Acute Kidney Damage Associated With Covid-19mentioning
confidence: 99%
“…Some authors, including ourselves, believe that the occurrence of proteinuria and hematuria in a COVID-19 patient are independent predictors of the development of the critical stage of the disease [6,13,20]. Similarly, literature data also indicate that AKI has been diagnosed in patients with COVID-19 more frequently than cardiovascular (23%) and liver (23%) diseases [11][12][13][14]21]. Of the patients who developed AKI due to coronavirus infection, one in four patients required continuous hemodialysis, and 12 (80%) patients died within the first week of admission [2,5,9,22].…”
Section: Discussionmentioning
confidence: 96%
“…It has previously been established that AKI is a predictor of poor prognosis in hospitalized patients with COVID-19 [6,9,11]. The high prevalence of AKI in the severe COVID-19 group [1,3,12] and the increased mortality risk in patients with AKI [4,13,14] highlight the need to further explore predictors of kidney damage in this population. Additionally, most studies have investigated the prognosis without considering the timing of kidney failure onset.…”
Section: Introductionmentioning
confidence: 99%
“…The first of these studies showed the incidence of AKI being significantly lower in the second wave. [ 36 ] But the Italian cohort showed similar rates of AKI in both waves of COVID-19. [ 37 ] While, we reported previously in our comparison of waves that similar rises in serum urea levels were observed during both waves, while peak levels were attained early in the second wave, despite creatinine was deranged equally in both waves.…”
Section: Discussionmentioning
confidence: 99%